Batteries and electrical devices
Patent Information
- Application Number
- JP2024519799
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-01-09
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2043-08-30
AI Technical Summary
【0021】 従来の技術と比較すると、本願は、負極シートの非ファラデー容量(Cdl nF)と該負極シートに含まれる負極活物質の球形度(S)との関係を調整することによって、負極活物質の比表面積を効果的に低減し、そのタップ密度を向上させ、それにより、負極シートが比較的高い密度を有しながら、過圧現象が生じないようにする。さらに、負極シートの負極活物質が圧延する間に受ける機械的応力を低減し、電解液との反応面積を低減し、良好な保液性能及び電解液への含浸効果を得ることができ、それにより、ガス発生及び膨潤現象の発生を回避し、電池に優れた急速充放電性能、良好な倍率性能とサイクル性能を持たせた。また、本願の負極活物質顆粒は孔を有するため、負極シートの保液性能及び電解液の含浸効果をさらに高め、電池の総合性能を向上させることができる。
Smart Images

Figure 2025505912000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to a Chinese patent application filed with the China Patent Office on January 9, 2023, bearing application number 202310027089.X and entitled "Battery and Electrical Use Apparatus," the entire contents of which are incorporated herein by reference.
[0002] The present application relates to the field of new energy technology, specifically to batteries and electricity-using devices. [Background technology]
[0003] Lithium ion batteries have advantages such as high energy, high power performance, low self-discharge, and long cycle life, and are therefore widely used in various fields. In order to increase the energy density of lithium ion batteries, the gram capacity and compression density of the negative electrode sheet can be increased by compression. However, the overpressure phenomenon caused by compression slows down the rate at which the negative electrode sheet is impregnated with the electrolyte, and the liquid absorption performance, liquid retention performance, and impregnation effect of the negative electrode sheet are reduced, which are disadvantageous to improving the energy density and cycle performance of lithium ion batteries. Summary of the Invention [Problem to be solved by the invention]
[0004] The present application provides a battery and an electrical device, which solves the problem of poor electrolyte impregnation and absorption effects due to overpressure on the negative electrode sheet of the battery, thereby solving the problem of low battery energy density, multiplication factor and cycle performance. [Means for solving the problem]
[0005] In a first aspect, the present application provides a battery, which includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte.
[0006] Here, the positive electrode sheet includes a positive electrode current collector and a positive electrode film piece disposed on at least one surface of the positive electrode current collector, and the positive electrode film piece includes a positive electrode active material.
[0007] The negative electrode sheet includes a negative electrode current collector and a negative electrode film piece disposed on at least one surface of the negative electrode current collector, the negative electrode film piece including a negative electrode active material. The negative electrode active material includes negative electrode active material granules having pores.
[0008] The non-Faraday capacity of the negative electrode sheet is Cdl nF, and the sphericity of the negative electrode active material is S, which satisfies the following characteristics: 0.5≦Cdl×S≦5.
[0009] In the embodiment of the present application, 0.5≦Cdl≦8 and 0.2≦S≦0.9.
[0010] In the embodiment of the present application, the pore size of the negative electrode active material is r nm, and Cdl and r satisfy the following characteristics: 1.2≦0.1×r+Cdl≦10.
[0011] In the examples of the present application, the pore size distribution of the negative electrode active material satisfies 2≦r≦20.
[0012] In the examples of the present application, the pore size distribution of the negative electrode active material satisfies the requirement that the pore size distribution of the negative electrode active material has at least one peak in the region of 2 nm to 6 nm.
[0013] In the present embodiment, the negative electrode active material includes elemental sulfur.
[0014] In the present embodiment, the liquid absorption time of the negative electrode membrane piece is Tmin, and the compressed density of the negative electrode membrane piece is PDg / cm 3 and 0.3≦T×PD≦5.8 is satisfied.
[0015] In the present embodiment, 0.25≦T≦3.5 and 1.1≦PD≦1.7.
[0016] In the present embodiment, the negative electrode active material has a Dv50 of D1 μm, the positive electrode active material has a Dv50 of D2 μm, and D1 and D2 satisfy at least one of the following characteristics: (c) 1≦D1 / D2≦36; (d) 6≦D1≦18; (e) 0.5≦D2≦8.
[0017] In the examples of the present application, the powder compression density of the negative electrode active material at a pressure of 30 KN is P1g / cm 3 The powder compaction density of the positive electrode active material at a pressure of 30KN is P2g / cm 3 The relationship between P1 and P2 satisfies the following characteristic: 1.5≦P2 / P1≦2.5.
[0018] Preferably, 1.5≦P1≦2.0 and 2≦P2≦4.
[0019] In an embodiment of the present application, the negative electrode active material includes a carbon material, and the carbon material includes graphite.
[0020] In a second aspect, an embodiment of the present application further provides an electricity-using device, which includes the battery in the above embodiment, and the battery is used as a power supply for the electricity-using device. Effect of the Invention
[0021] Compared with the conventional technology, the present invention effectively reduces the specific surface area of the negative electrode active material and improves its tap density by adjusting the relationship between the non-Faraday capacity (Cdl nF) of the negative electrode sheet and the sphericity (S) of the negative electrode active material contained in the negative electrode sheet, thereby making the negative electrode sheet have a relatively high density and prevent overpressure. In addition, the mechanical stress that the negative electrode active material of the negative electrode sheet receives during rolling is reduced, the reaction area with the electrolyte is reduced, and good liquid retention performance and electrolyte impregnation effect can be obtained, thereby avoiding the occurrence of gas generation and swelling phenomena, and giving the battery excellent rapid charge / discharge performance, good multiplication performance and cycle performance. In addition, since the negative electrode active material granules of the present invention have pores, the liquid retention performance and electrolyte impregnation effect of the negative electrode sheet can be further improved, and the overall performance of the battery can be improved.
[0022] The electric power-using device provided by the embodiment of the present application has all the technical features and inventive effects of the above battery, and will not be described further herein. [Brief description of the drawings]
[0023] [Figure 1] FIG. 2 is a scan rate-current scatter diagram according to Example 1 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present application provides a battery and an electric device, and in order to make the purpose, technical solution and effects of the present application clearer and more precise, the present application will be described in more detail below by way of examples with reference to the drawings. It should be understood that the specific examples described in the present specification are merely for the purpose of illustrating the present application, and are not intended to limit the present application.
[0025] During the applicant's research, it was found that if overpressure occurs during the rolling process of the negative electrode sheet when manufacturing a battery, it will affect the impregnation effect of the negative electrode sheet with the electrolyte and the liquid absorption performance of the negative electrode sheet, thereby affecting the battery's power supply performance and cycle performance.
[0026] In order to solve the above problems, the embodiments of the present application provide a battery (or lithium ion battery), which has a pore structure in the negative active material granules, and at the same time, adjusts the non-Faraday capacity (Cdl nF) of the negative electrode sheet and the sphericity (S) of the negative electrode active material contained in the negative electrode sheet, thereby effectively reducing the specific surface area of the negative electrode active material and improving its tap density, so that the negative electrode sheet has a relatively high density while preventing overpressure phenomenon, and also reduces the mechanical stress that the negative electrode active material of the negative electrode sheet receives during rolling, reduces the reaction area with the electrolyte, and achieves good electrolyte retention performance and electrolyte impregnation effect, thereby providing the battery with excellent rapid charge / discharge performance, good multiplication performance and cycle performance.
[0027] An embodiment of the present application provides a battery, which includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. The separator is disposed between the positive electrode sheet and the negative electrode sheet.
[0028] Here, the positive electrode sheet includes a positive electrode current collector and a positive electrode film piece disposed on at least one surface of the positive electrode current collector, and the positive electrode film piece includes a positive electrode active material.
[0029] The negative electrode sheet includes a negative electrode current collector and a negative electrode film piece disposed on at least one surface of the negative electrode current collector, the negative electrode film piece includes a negative electrode active material, the negative electrode active material includes negative electrode active material granules having pores, the non-Faraday capacity of the negative electrode sheet is Cdl nF, and the sphericity of the negative electrode active material is S, and the following characteristics are satisfied: 0.5≦Cdl×S≦5.
[0030] In some embodiments of the present application, the non-Faraday capacity of the negative electrode sheet is Cdl nF, the sphericity of the negative electrode active material is S, and both satisfy 1≦Cdl×S≦4.5. When 1≦Cdl×S≦4.5, the specific surface area and tap density of the negative electrode sheet can be further adjusted, so that the negative electrode sheet has a relatively high density and does not cause overpressure phenomenon, and at the same time, the reaction area between the negative electrode sheet and the electrolyte can be in a suitable range, and the overall performance of the battery can be further improved.
[0031] In some embodiments of the present application, the non-Faraday capacity of the negative electrode sheet is Cdl nF, and the sphericity of the negative electrode active material is S, both of which satisfy 1.5≦Cdl×S≦4. When 1.5≦Cdl×S≦4, the overall performance of the battery can be further improved.
[0032] In some embodiments of the present application, the non-Faraday capacity of the negative electrode sheet is Cdl nF, and the sphericity of the negative electrode active material is S, both of which satisfy 2≦Cdl×S≦3.
[0033] The method for testing the non-Faraday capacity Cdl of the negative electrode sheet in the examples of the present application includes the following steps.
[0034] S1, the button battery assembly process includes the following steps: the obtained negative electrode sheet is dried, cut into small circular sheets, weighed, and then transferred to a vacuum oven and dried at 100°C for 8h, and then transferred to a glove box filled with argon gas for half-cell assembly.
[0035] In S2, a step of confirming the non-Faraday potential range, a cyclic voltammogram (CV) test is performed on the assembled button battery to confirm the non-Faraday potential range of the button battery, where the voltage range is 0.005 to 3.0 V and the scan rate is 0.1 to 1 mV / s.
[0036] In S3, the non-Faraday range cathodic scanning step, a linear scan voltammogram (LSV) test is performed by arbitrarily selecting the linear step potential range in S2, and the voltage-current curve is collected from high potential to low potential, where the potential range is 2.6-2.7V and the scan rate is 0.05-5mV / s. Then, a median value U of the potential range is selected at a certain scan rate V1 (the certain scan rate may be 0.1mV / s, 0.2mV / s, 0.5mV / s, 1mV / s, 2mV / s, etc.) to obtain the corresponding current value, and a scan rate-current scatter diagram is obtained.
[0037] In step S4, calculating the non-Faraday capacitance, a linear function is obtained by fitting the scan rate-current scatter diagram collected in S3, and the slope K of the linear function is the non-Faraday capacitance value Cdl of the negative electrode sheet in the cathode scan direction.
[0038] According to the above test, the non-Faraday capacity (Cdl nF) of the negative electrode sheet in the examples of the present application is 0.5 to 8 nF. The non-Faraday capacity Cdl nF of the negative electrode sheet may be 1 to 6 nF, 2 to 5 nF, or 3 to 4 nF. The basic unit of capacity is the Faraday, abbreviated as the modulus (F). 1F=1000 mF, 1 mF=1000 μF, 1 μF=1000 nF. Therefore, 1 nF (nFal) = 10 -9 It's F.
[0039] The sphericity S of the negative active material in the negative electrode sheet in the embodiment of the present application is measured using a dynamic image granule analyzer. Specifically, the method of obtaining the negative active material from the negative electrode sheet may be as follows: The secondary battery is discharged to the lower voltage limit at a constant current of 0.04C, disassembled to obtain a negative electrode sheet, immersed in a dimethyl carbonate (DMC) solution, then washed several times with deionized water, the upper layer solution is removed, the lower layer solution is left to dry, and finally, heat treated at 800°C for 2 hours in an argon atmosphere to obtain the above test sample.
[0040] The more a granule is spherical in shape, the closer its sphericity is to 1.
[0041] In some embodiments of the present application, the sphericity S of the negative electrode active material is 0.2 to 0.9. For example, the numerical range of S may be any of 0.2, 0.3, 0.35, 0.4, 0.43, 0.45, 0.48, 0.5, 0.53, 0.55, 0.58, 0.6, 0.63, 0.65, 0.68, 0.7, 0.73, 0.75, 0.78, 0.8, 0.85, and 0.9, or a range consisting of any two numbers therein. When the sphericity of the negative electrode active material is in the above range, the morphology of the negative electrode active material granules can be excellent, and the overall performance of the battery can be improved. In some embodiments of the present application, the sphericity S of the negative electrode active material is 0.3 to 0.85. When the sphericity S is 0.3 to 0.85, the overall performance of the battery can be further improved.
[0042] In some embodiments of the present application, the sphericity S of the negative electrode active material is 0.4 to 0.78.
[0043] In some embodiments of the present application, the sphericity S of the negative electrode active material is 0.45 to 0.73.
[0044] Lithium-ion batteries undergo electrochemical reactions during use. Electrochemical reactions include faradaic reactions, in which the oxidation state of the active material changes and charges move into the active material, and non-faradaic reactions, in which ions physically adsorb and desorb on the surface of the active material to store and release charges. Faradaic reactions refer to the change in the oxidation state of the active material, and charges move into the active material through the electrode interface by passing through a double charge layer. Non-faradaic reactions refer to the transfer of charges that does not pass through the electrode interface, in which ions physically adsorb and desorb on the electrode surface to store and release charges.
[0045] The applicant found that the non-Faraday capacity Cdl reflects the number of active points in the negative electrode sheet, and during the use of the battery, the non-Faraday capacity Cdl nF of the negative electrode sheet needs to be controlled within an appropriate range. When the Cdl value is within a certain range, the larger the Cdl value, the more electrochemically active points there are, which is favorable for the contact between the active material and the electrolyte, and can accelerate the conduction speed of ions and electrons, reduce the charge transport resistance, and efficiently improve the multiplication performance. Meanwhile, the sphericity S of the negative electrode active material affects the isotropy of the negative electrode active material granules, which affects the release direction and path of lithium ions, and the sphericity affects the distribution of the negative electrode active material in the negative electrode sheet, which affects the contact between the negative electrode active materials. The negative electrode active material granules have a pore structure, which can further increase the impregnation speed and liquid retention performance of the negative electrode sheet, and the synergistic effect of the three can effectively improve the overall performance of the battery. Therefore, by adjusting the negative active material and the negative sheet, the non-Faraday capacity Cdl nF of the negative sheet and the sphericity S of the negative active material are within the range of 0.5≦Cdl×S≦5, the specific surface area of the negative active material is effectively reduced, the tap density is improved, the negative sheet has a relatively high density and does not cause overpressure, the mechanical stress that the negative active material of the negative sheet receives during rolling is reduced, the reaction area with the electrolyte is reduced, and the negative active material has good liquid retention performance, thereby preventing gas generation and swelling, and thus providing the lithium ion battery with excellent rapid charge / discharge performance and cycle performance. In addition, the negative active material includes a graphite material, and the negative active material exists as negative active material granules, and between these negative active material granules, lithium ions can quickly form a path between the graphite layers, and the solid-phase diffusion path of lithium ions is shortened, thereby improving the charging rate of the negative sheet, realizing rapid charging, and improving high-speed charging performance.
[0046] In some embodiments of the present application, the pore size value of the negative electrode active material is r nm, and the non-faradaic capacity of the negative electrode sheet is Cdl nF, and the relationship between the two satisfies the following characteristics: 1.2≦0.1×r+Cdl≦10. The pore size and non-faradaic capacity of the negative electrode active material affect the fast charging ability and cycle life of the lithium ion battery. Within a certain range, the higher the non-faradaic capacity of the negative electrode active material, the more active sites on its surface will be, so that the contact with the electrolyte will be sufficient, the resistance of the lithium ion battery will be reduced, and the capacity will be improved. In addition, a suitable pore size can prevent the rolled granules from being crushed, and shorten the solid-phase diffusion path of lithium ions in the negative electrode active material, thereby improving the kinetic performance of the lithium ion battery. In the embodiments of the present application, the pore size of the negative electrode active material and the non-faradaic capacity of the negative electrode sheet can be adjusted so that lithium ions can be smoothly inserted into the negative electrode active material through the pore path during the subsequent electrochemical reaction, thereby improving the cycle performance of the lithium ion battery. On the other hand, the pore size buffers the volume change during the charge and discharge process of the lithium ion battery and improves the cycle performance of the lithium ion battery. Therefore, the present application appropriately adjusts the relationship between the pore size of the negative electrode active material and the non-Faraday capacity, and controls the relationship between the two within the range of 1.2≦0.1×r+Cdl≦10, thereby achieving the energy density, fast charging performance and long cycle life of the lithium ion battery and preventing overpressure from adversely affecting these performances of the lithium ion battery.
[0047] In some embodiments of the present application, the pore size value of the negative active material is r nm, the non-Faraday capacity of the negative sheet is Cdl nF, and satisfies 2≦0.1×r+Cdl≦8. When 2≦0.1×r+Cdl≦8, the pore size and non-Faraday capacity of the negative active material are in a more suitable range, which further influences the impregnation performance of the electrolyte and the reaction situation with the electrolyte, and improves the overall performance of the battery.
[0048] In some embodiments of the present application, the pore size value of the negative electrode active material is r nm, the non-Faraday capacity of the negative electrode sheet is Cdl nF, and 3≦0.1×r+Cdl≦7 is satisfied.
[0049] In some embodiments of the present application, the pore size value of the negative electrode active material is r nm, the non-Faraday capacity of the negative electrode sheet is Cdl nF, and 4≦0.1×r+Cdl≦6 is satisfied.
[0050] Preferably, in some embodiments of the present application, the size of the pore diameter value r of the negative electrode active material may be 2 nm to 20 nm. For example, the numerical range of r nm may be any one of 2 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 4.8 nm, 5 nm, 5.3 nm, 5.5 nm, 5.8 nm, 6 nm, 6.5 nm, 6.8 nm, 7 nm, 7.5 nm, 7.8 nm, 8 nm, 8.5 nm, 9 nm, 10 nm, 11 nm, 12 nm, 12.5 nm, 13 nm, 13.5 nm, 14 nm, 14.5 nm, 15 nm, 15.5 nm, 16 nm, 17 nm, 18 nm, 19 nm, and 20 nm, or a range consisting of any two numbers therein.
[0051] In some embodiments of the present application, the pore size of the negative electrode active material is 3 nm to 18 nm.
[0052] In some embodiments of the present application, the pore size value of the negative electrode active material is 3.5 nm to 12 nm.
[0053] In some embodiments of the present application, the pore size of the negative electrode active material is between 4 nm and 10 nm.
[0054] In some embodiments of the present application, the pore size of the negative electrode active material is 5 nm to 8 nm.
[0055] Since the negative electrode active material has an appropriate pore size, both the pressure resistance of the negative electrode active material granules and the diffusion of the negative electrode active material in the electrolyte can be within preferred ranges, thereby enhancing non-Faraday reactions and improving the kinetic performance of lithium ions.
[0056] In some embodiments of the present application, the pore size distribution of the negative electrode active material preferably has at least one peak in the region of 2 nm to 6 nm. When there is a peak in the region of 2 nm to 6 nm, the pore size distribution of the negative electrode active material becomes better, and the overall performance of the battery can be further improved.
[0057] Preferably, in some embodiments of the present application, the negative electrode active material layer contains elemental sulfur.
[0058] Preferably, in some embodiments of the present application, the negative electrode active material includes elemental sulfur.
[0059] Preferably, in some embodiments of the present application, the negative electrode active material comprises a carbon material.
[0060] Preferably, in some embodiments of the present application, the negative electrode active material comprises graphite.
[0061] Preferably, in some embodiments of the present application, the negative electrode active material comprises synthetic graphite.
[0062] Preferably, in some embodiments of the present application, the coke feedstock used in the negative electrode active material includes a sulfur-containing material.
[0063] Preferably, in some embodiments of the present application, the sulfur content of the coke raw material used in the negative electrode active material may be 0.1wt% to 4wt%. For example, the numerical range of the sulfur content may be any one of 0.1wt%, 0.2wt%, 0.3wt%, 0.5wt%, 0.7wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.3wt%, 1.5wt%, 1.6wt%, 1.8wt%, 2.0wt%, 2.1wt%, 2.5wt%, 2.7wt%, 3.0wt%, 3.2wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.8wt%, and 4.0wt%, or a range consisting of any two of the numbers therein.
[0064] Preferably, in some embodiments of the present application, the sulfur content of the coke raw material used in the negative electrode active material may be 0.2 to 3 wt %.
[0065] Preferably, in some embodiments of the present application, the sulfur content of the coke raw material used in the negative electrode active material may be 0.5 to 2.5 wt %.
[0066] Preferably, in some embodiments of the present application, the sulfur content of the coke raw material used in the negative electrode active material may be 1 to 2 wt %.
[0067] Preferably, in some embodiments of the present application, the volatile matter content of the coke raw material may be 5 to 15 wt%. For example, the numerical range of the volatile matter content of the coke raw material may be any one of 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, 10 wt%, 10.5 wt%, 11 wt%, 11.5 wt%, 12 wt%, 12.5 wt%, 13 wt%, 13.5 wt%, 14 wt%, 14.5 wt%, and 15 wt%, or a range consisting of any two numbers therein.
[0068] Preferably, in some embodiments of the present application, the volatile matter content in the coke raw material may be 6 wt% to 12 wt%.
[0069] Preferably, in some embodiments of the present application, the content of the volatile matter in the coke raw material may be 8 wt% to 10 wt%.
[0070] Preferably, in some embodiments of the present application, the coke raw material may be selected from coke, petroleum coke (e.g., petroleum pitch, etc.), coal tar, asphalt coke (coal pitch, etc.), etc. The coke raw material having specific raw material properties is selected in order to control the raw material properties of the negative electrode active material to obtain negative electrode active material granules having a suitable pore structure.
[0071] The sulfur content of the coke raw material is measured by energy dispersive X-ray fluorescence spectroscopy, and the volatile content is measured by the SH / T0026-1990 petroleum coke volatile content measurement method. Sulfur is harmful to coking, gasification, combustion and storage and transportation. High or low volatile content affects the production efficiency of raw materials and increases coal consumption. The sulfur entering during coking reduces the production capacity of coke, and the sulfur dioxide generated during gasification corrodes equipment, affects operation and product quality, and pollutes the environment. Therefore, selecting coke raw materials with appropriate sulfur content can reduce the impact on the environment, reduce the impurity content, improve isotropy, and ensure the excellent multiplication performance of the manufactured lithium-ion battery, as well as a relatively low impedance and its own stability during the cycle process. In addition, the sulfur content of the coke raw material is also related to the formation of an appropriate pore size in the negative electrode active material during rolling. When the negative electrode active material forms an appropriate pore size after being rolled, it has an appropriate compaction density, enhances the non-Faraday reaction, improves the kinetic performance of lithium ions, and alleviates the overpressure phenomenon.
[0072] Preferably, in some embodiments of the present application, the Harvestability Index HGI of the coke raw material may be 30 to 100. For example, the Harvestability Index HGI of the coke raw material may be in the range of any one of 30, 32, 35, 36, 38, 40, 44, 45, 48, 50, 52, 55, 56, 58, 60, 65, 70, 75, 80, 85, 90, 93, 95, 98, and 100, or a range consisting of any two of the numbers therein.
[0073] Preferably, in some embodiments of the present application, the coke raw material may have a Harvestability Index (HGI) of 40-90.
[0074] Preferably, in some embodiments of the present application, the coke raw material may have a Harvestability Index (HGI) of 50-80.
[0075] Harvestability index (HGI) refers to the ratio of energy consumed when crushing a sample to a specified number of particles and a standard sample under air-drying conditions to the same fineness, which is used to measure the abrasiveness of the coke raw material, and the magnitude of the value reflects the difficulty of crushing different types of coke raw materials. Harvestability index is measured by the hard glove method and is a hardness index for measuring coke raw materials. The softer the coke raw material is, the larger the HGI value is relatively, and the easier the coke raw material is to be crushed, and the higher the compressed density of the obtained negative electrode active material is. However, if the Harvestability index is too large or too small, it has a certain effect on the negative electrode active material, so it is necessary to control it within a specific range. The applicant has found through research that if the Harvestability index (HGI) of the coke raw material is in the range of 30 to 100, the compressed density and pore size distribution of the negative electrode active material can be controlled within an appropriate range.
[0076] Preferably, in some embodiments of the present application, the liquid absorption time of the negative electrode membrane piece is Tmin, and the compressed density of the negative electrode membrane piece is PDg / cm 3 The relationship between the two satisfies the following characteristics: 0.3≦T×PD≦5.8. For example, the numerical range of the value of T×PD may be any of 0.3, 0.4, 0.6, 0.7, 1.0, 1.2, 1.5, 1.8, 2.0, 2.3, 2.5, 2.8, 3, 3.5, 4.0, 4.4, 5.0, 5.2, 5.5, 5.6, and 5.8, or a range consisting of any two numbers therein. When the value of T×PD is within the above range, the degree of extrusion between the negative electrode active material granules and the porosity of the negative electrode sheet are in an appropriate range, and the negative electrode sheet can ensure the impregnation performance of the electrolyte, reduce polarization during the cycle process of the battery, and mitigate the increase in the internal resistance of the battery.
[0077] Preferably, in some embodiments of the present application, the liquid absorption time of the negative electrode membrane piece is Tmin, and the compressed density of the negative electrode membrane piece is PDg / cm 3 and the relationship between them may be 0.5≦T×PD≦5.5.
[0078] Preferably, in some embodiments of the present application, the liquid absorption time of the negative electrode membrane piece is Tmin, and the compressed density of the negative electrode membrane piece is PDg / cm 3 and the relationship between the two may be 1≦T×PD≦5.
[0079] Preferably, in some embodiments of the present application, the liquid absorption time of the negative electrode membrane piece is Tmin, and the compressed density of the negative electrode membrane piece is PDg / cm 3 and the relationship between them may be 2≦T×PD≦4.
[0080] Preferably, in some embodiments of the present application, the liquid absorption time T of the negative electrode membrane piece may be 0.25 to 3.5 min (i.e., 0.25≦T≦3.5, the same applies below). For example, it may be any one of 0.25, 0.3, 0.6, 0.7, 1.1, 1.5, 2, 3, 3.2, and 3.5, or a range consisting of any two of these numbers.
[0081] Preferably, in some embodiments of the present application, the liquid absorption time T of the negative electrode membrane piece may be 0.5 to 3 minutes.
[0082] Preferably, in some embodiments of the present application, the liquid absorption time T of the negative electrode membrane piece may be 1 to 2.5 minutes.
[0083] Preferably, in some embodiments of the present application, the compressed density PD of the negative electrode membrane piece is 1.1 to 1.7 g / cm 3 (That is, 1.1≦PD≦1.7.) For example, the numerical range of the value of PD may be any one of 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, and 1.7, or a range consisting of any two of these numbers.
[0084] The liquid absorption time of the negative electrode membrane piece can be measured by an optical contact angle measuring device, and the method of measuring the liquid absorption time is as follows. When measuring the liquid absorption time, a drop (about 10 μL) of electrolyte is dropped vertically using a micro sampler, and at the same time, a stopwatch is started to measure the time when the electrolyte is completely impregnated after diffusion, and the time is recorded as the liquid absorption time of the negative electrode membrane piece. The longer the liquid absorption time, the worse the impregnation performance of the negative electrode sheet. The compressed density is closely related to the specific capacity, efficiency, internal resistance and cycle performance of the battery of the negative electrode sheet. The higher the compressed density, the higher the energy density, but the greater the degree of extrusion between the active material granules and the smaller the porosity of the electrode sheet, making it difficult for the electrolyte to be impregnated, the worse the electrolyte retention capacity of the battery, the longer the liquid absorption time of the negative electrode membrane piece, and the greater the polarization and the higher the internal resistance during the cycle process. Therefore, in order to improve the performance of the lithium ion battery, it is necessary to control the compressed density of the negative electrode sheet and consider the effect of the liquid absorption time on the performance of the lithium ion battery.
[0085] Preferably, in some embodiments of the present application, the Dv50 of the negative electrode active material is D1μm, and the Dv50 of the positive electrode active material is D2μm, and the relationship between D1 and D2 satisfies the following characteristics, 1≦D1 / D2≦36. Preferably, it may be any of 1, 3, 4, 6, 7, 8, 9, 10, 11, 15, 21, 23, 25, 27, 30, 32, 36, or a range consisting of any two numbers therein. By controlling the value of the particle size ratio of the positive electrode active material and the negative electrode active material within the range of 1 to 36, both the positive electrode sheet and the negative electrode sheet have relatively high electron transport performance and lithium ion transport performance, and the electrochemical reaction between the positive electrode sheet and the negative electrode sheet is well matched, and the lithium ion battery has relatively high charge and discharge performance under high magnification.
[0086] Preferably, in some embodiments of the present application, the relationship between D1 and D2 may be 2≦D1 / D2≦35.
[0087] Preferably, in some embodiments of the present application, the relationship between D1 and D2 may be 5≦D1 / D2≦30.
[0088] Preferably, in some embodiments of the present application, the relationship between D1 and D2 may be 10≦D1 / D2≦20.
[0089] Preferably, in some embodiments of the present application, D1 is 6≦D1≦18. Preferably, D1 may be any one of 6, 7, 8, 9, 10, 11, 12, 15, 16, and 18, or any two of them. When the particle size of the negative electrode active material granules is within the above range, the degree of compactness of the structure forming the negative electrode membrane piece is in an appropriate range, which is favorable for the penetration of the electrolyte, and the interface resistance of the negative electrode active material granules is in an appropriate range, so that the dynamic performance of the lithium ion battery is excellent. Meanwhile, the particle size of the negative electrode active material granules affects the dispersibility of the active material granules in the slurry, so that the aggregation of the negative electrode active material granules is reduced, the surface density distribution is more uniform, the adhesion of the electrode sheet is appropriate, and the electronic and electrical conduction ability of the negative electrode sheet is relatively good, so that the dynamic performance and cycle life of the battery can be improved.
[0090] Preferably, in some embodiments of the present application, 0.5≦D2≦8. Or, it may be any of 0.5, 1, 1.5, 2, 2.5, 2.7, 3.0, 3.5, 3.8, 4, 4.3, 4.5, 4.8, 5, 5.5, 5.8, 6, 6.3, 6.5, 7, 8, or any two of them. When the particle size of the positive electrode active material granule is in the above range, the electrolyte penetration performance of the positive electrode membrane piece is strong, the liquid phase diffusion performance of lithium ions is in an appropriate range, and the solid phase conduction ability of lithium ions in the particles is strong, so that the overall performance of the lithium ion battery can be effectively guaranteed.
[0091] The Dv50 of the positive and negative active materials can be tested using a laser granulometer.
[0092] Preferably, in some embodiments of the present application, the powder compaction density of the negative electrode active material at 30 KN is P1g / cm 3 The powder compression density of the positive electrode active material at 30KN is P2g / cm 3The relationship between P1 and P2 satisfies the following characteristics, 1.5≦P2 / P1≦2.5. For example, the numerical range of the value of P2 / P1 may be any of 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, and 2.5, or any two of them. In the embodiment of the present application, the ratio of the powder compaction density at 30 KN pressure between the positive electrode active material and the negative electrode active material is controlled within the range of 1.5 to 2.5, which is advantageous for the lithium ions to diffuse inside and between the active materials, improve the solid-phase conduction ability of the lithium ions, reduce the resistance of the lithium ion battery, and improve the rapid charging ability and cycle life of the lithium ion battery. Preferably, in some embodiments of the present application, the relationship between P1 and P2 satisfies 1.6≦P2 / P1≦2.4.
[0093] Preferably, in some embodiments of the present application, the relationship between P1 and P2 satisfies 1.8≦P2 / P1≦2.2.
[0094] Preferably, in some embodiments of the present application, the relationship between P1 and P2 satisfies 1.9≦P2 / P1≦2.1.
[0095] Preferably, in some embodiments of the present application, 1.5≦P1≦2.0 may be satisfied, or may be a range consisting of any two of the numbers 1.6, 1.7, 1.8, and 1.9. When P1 satisfies the above range, the pore structure and morphology, such as sphericity, of the negative electrode active material are both in a good state, which can improve the pore structure of the negative electrode sheet and make the battery in a good state.
[0096] Preferably, in some embodiments of the present application, P2 may be 2≦P2≦4, or may be a range consisting of any two of the following numbers: 2.1, 2.2, 2.5, 2.8, 3, and 3.2. When P2 satisfies the above range, the matching degree between the positive electrode sheet and the negative electrode sheet is higher, and the battery has better overall performance.
[0097] The compression density test of the negative active material powder was performed with reference to GB / T 24533-2019 Lithium-ion battery graphite-based negative electrode material. The test conditions were as follows: 1g of negative active material was weighed, the pressure speed was 8mm / min, the pressure holding time was 30s, the pressure after decompression was 20N, the pressure reduction speed was 30mm / min, and the holding time after decompression was 10s.
[0098] The test conditions for the positive electrode active material were as follows: 1.5 g of positive electrode active material was weighed, the pressurization speed was 1 mm / min, the pressurization and holding time was 60 s, the pressure after depressurization was 30 N, the depressurization speed was 4 mm / min, and the holding time after depressurization was 10 s.
[0099] Preferably, in some embodiments of the present application, the positive electrode active material includes one or more of a lithium iron phosphate material, a lithium manganese iron phosphate material, a lithium nickel cobalt manganese material, and a lithium nickel cobalt aluminum material.
[0100] The lithium iron phosphate material is LiFePO4 (abbreviated as LFP).
[0101] The chemical formula of lithium manganese iron phosphate material is Li y Fe x Mn 1-x PO4, 0.9≦y≦1.2, 0.2≦x≦0.5. For example, LiFe 0.2 Mn 0.8 PO4, LiFe 0.3 Mn 0.7 PO4, LiFe 0.4 Mn 0.6 PO4 or LiFe 0.5 Mn 0.5 It may also be PO4.
[0102] Lithium nickel cobalt manganese material is Li d Ni a Co b Mn c A eIt may also be O2, A contains at least one of Al, Zr, Ti, B, Mg, V, Cr, Zn, Y, W, Nb or La, 0.4 < a < 1, 0 < b < 1, 0 < c < 1, 0.9 ≤ d ≤ 1.1, 0 ≤ e ≤ 0.1, and a + b + c = 1. For example, it may be NCM523, NCM622, NCM811, etc.
[0103] The lithium nickel cobalt aluminum material is Li d1 Ni a1 Co b1 Al c1 A e1 It may also be O2, A contains at least one of Zr, Ti, B, Mg, V, Cr, Zn, Y, W, Nb or La, 0.4 < a1 < 1, 0 < b1 < 1, 0 < c1 < 1, 0.9 ≤ d1 ≤ 1.1, 0 ≤ e1 ≤ 0.1, and a1 + b1 + c1 = 1.
[0104] The present application further provides an electrical appliance, and this electrical appliance includes the battery according to any of the above embodiments, and the battery is used as the power supply of the electrical appliance. The electrical appliance according to the present application includes, but is not limited to, a backup power supply, a motor, an electric vehicle, an electric motorcycle, an assist bicycle, a bicycle, an electric tool, a large household battery, etc.
[0105] Hereinafter, it will be described based on specific embodiments. It should be understood that these embodiments are merely for explaining the present application and are not intended to limit the present application.
[0106] Example 1
[0107] This example provides a method for manufacturing a negative electrode sheet, and this method for manufacturing a negative electrode sheet includes the following steps.
[0108] 1. The steps of preparing the negative electrode active material include the following: Select raw petroleum coke with sulfur content of 2wt%, volatile content of 8wt%, and HGI value of 60, and then grind it with a roller mill, pre-mix and other pre-treatment processes, so that the particle size after grinding is 8-10μm. The ground product is subjected to high-temperature graphitization treatment under a protective atmosphere, the temperature is 2800-3000℃, and the maximum temperature is kept at 3000℃ for 36h, and the protective atmosphere is argon. Then, the product is polished and shaped in a continuous shaping system for 8h, the surface of the product granules is smooth and flat, and a negative electrode active material (particle form) with a sphericity S of 0.7 and a particle size Dv50 (D1) of 12μm is obtained. The powder compression density P1g / cm of the negative electrode active material at a pressure of 30KN 3 is 1.76g / cm 3 It is.
[0109] 2. The negative electrode slurry preparation step includes the following steps: Mix the negative electrode active material (finished artificial graphite), conductive agent (carbon black), adhesive (sodium carboxymethyl cellulose), and additive (styrene butadiene rubber) in a mass ratio of 96.5:1.5:1.5:0.5, and then mix with a solvent (deionized water) in a specific ratio using a vacuum mixer to uniformly mix to prepare the negative electrode slurry.
[0110] 3. The steps of manufacturing the negative electrode sheet include: The prepared negative electrode slurry is uniformly coated on both sides of the negative electrode current collector (copper foil), and then baked and dried at 90-110°C, and then rolled and cut to obtain the negative electrode sheet. The compressed density of the negative electrode film piece formed from the negative electrode slurry of the negative electrode sheet is 1.6 g / cm 3 By adjusting the rolling time and the rolling force, the non-Faraday capacity of the negative electrode sheet can be adjusted.
[0111] This embodiment further provides a method for manufacturing a lithium ion battery having the above negative electrode sheet, which includes the following steps:
[0112] After the negative and positive electrode sheets are dried, they are combined with a separator (PP film) and wound on a winding machine to produce a wound core. The positive electrode aluminum tab and the negative electrode copper-nickel plated tab are welded to the electric core. The welded electric core is then packaged in a pouch-formed aluminum plastic film. The lithium-ion battery is then manufactured after undergoing injection, chemical formation, and volume control.
[0113] Here, the method for manufacturing the positive electrode sheet includes the following steps.
[0114] The positive electrode slurry is prepared by mixing the positive electrode active material, positive electrode conductive agent, positive electrode adhesive and solvent (N-methylpyrrolidone, NMP) in the appropriate proportions. The prepared positive electrode slurry is uniformly coated on both sides of the positive electrode current collector (aluminum foil), which is then dried at 120°C, rolled and cut to obtain a positive electrode sheet.
[0115] Here, the particle diameter Dv50 (D2) of the positive electrode active material is 6.5 μm. The mass ratio of the positive electrode active material (NCM523), the positive electrode conductive agent (carbon black), and the positive electrode adhesive (polyvinylidene fluoride, PVDF) is mixed at 96:2:2. The powder compression density P2g / cm of the positive electrode active material at a pressure of 30 KN is 3 is 3.55g / cm 3 It is.
[0116] The electrolyte is produced by mixing ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) in a mass ratio of 1:1:1, and then adding 1 mol / L of LiPF6 and mixing uniformly to produce the electrolyte.
[0117] Using the negative electrode sheet obtained in this embodiment, the half cell (i.e., button cell) assembled from the negative electrode sheet and the lithium ion battery are subjected to corresponding tests. The test method is as follows:
[0118] 1. The non-faradaic capacity test includes the following steps: Step 1, the negative electrode sheet and the metallic lithium sheet are assembled into a button half-cell (i.e., a button cell). Step 2, the button cell is subjected to a CV test in the voltage range of 0.005-3.0V, the scanning rate is 0.1mV / s, and the non-faradaic potential range is ensured to be 2.6-2.7V. Step 3, the LSV test is then performed from 2.7V to 2.6V, the scanning rates are 0.1mV / s, 0.2mV / s, 0.5mV / s, 1mV / s, and 2mV / s, respectively, and the middle value of the potential range, 2.65V, is selected, and the corresponding current value is 1.72E. -05 , 1.62E -05 , 1.57E -05 , 1.52E -05 , 1.37E -05 Step 3: Create a scan rate-current scatter plot (shown in FIG. 1) and fit it to obtain a linear function. The slope of the linear function is −1.62E -06 The Cdl value in the cathode scanning direction of the negative electrode sheet according to this embodiment is 1.62 nF.
[0119] 2. The energy density test of lithium-ion batteries includes the following steps: The lithium-ion battery is left at 25°C for 30 min, fully charged at 1C, and fully discharged at 1C, and the actual discharge energy is recorded. The lithium-ion battery is weighed using an electronic balance. The ratio of the actual discharge energy at 1C to the weight is the actual energy density of the lithium-ion battery. Here, if the actual energy density is less than 80% of the target energy density, the actual energy density of the battery is considered to be very low. If the actual energy density is 80% or more but less than 95% of the target energy density, the actual energy density of the battery is considered to be low. If the actual energy density is 95% or more but less than 105% of the target energy density, the actual energy density of the battery is considered to be moderate. If the actual energy density is 105% or more but less than 120% of the target energy density, the actual energy density of the battery is considered to be high. If the actual energy density is 120% or more of the target energy density, the actual energy density of the battery is considered to be very high.
[0120] 3. The cycle performance test of the lithium-ion battery includes the following steps: Charge and discharge the lithium-ion battery at 25°C. Specifically, charge at a constant current of 1C, leave for 10 minutes, discharge at a constant current of 1C, record the first discharge capacity, charge and discharge the battery at 1C / 1C for 2000 cycles, record the 2000th discharge capacity of the battery, and divide the 2000th discharge capacity of the battery by the first discharge capacity of the battery to obtain the capacity retention rate of the battery after 2000 cycles of charge and discharge.
[0121] 4. The lithium-ion battery multiplier performance test includes the following steps: discharge the lithium-ion battery at 25°C with a constant current of 1C, leave it for 10 minutes, and charge it with a constant current of 3C, record the first discharge capacity, and divide the charge capacity by the first discharge capacity of charging and discharging at 1C / 1C to obtain the 3C multiplier performance of the battery.
[0122] 5. The pore size distribution and pore size value r of the negative electrode active material are obtained by measuring using mercury intrusion porosimetry.
[0123] 6. The compression density PD of the negative active material is measured by a compression density meter, and the measurement process refers to the national standard GB / T 24533-2019.
[0124] Other examples and comparative examples are tested with reference to the above methods.
[0125] Examples 2 to 5, Comparative Examples 1 to 2
[0126] The above examples and comparative examples provide a method for manufacturing a battery, which adjusts the parameters of the polishing and shaping step to adjust the sphericity S of the negative active material, and controls the parameters of the coke raw material of the negative active material as shown in the following table, while adjusting the non-Faraday capacity value Cdl of the negative sheet. The other steps and parameters are the same as those in Example 1. Please refer to the following table for specific parameter adjustments.
[0127] Examples 6 to 10
[0128] The above examples provide a method for manufacturing a lithium battery, which adjusts the pore size (r) of the negative active material. Other steps and parameters are the same as those of Example 1. The control over the pore size is mainly realized by selecting coke feedstock materials with different sulfur content and volatile matter. The control over the non-Faraday capacity value Cdl is adjusted together with the stirring process and rolling process, as long as it ensures that the Cdl value is within the range shown in Table 1.
[0129] Examples 11 to 15
[0130] The above embodiment provides a method for manufacturing a battery, which adjusts the roll gap and pressure of the rolling machine in the rolling step, and adjusts the compression density PD of the negative electrode membrane piece by adjusting the relevant parameters such as compression density, pore size, particle size, etc. of the powder. The other steps and parameters are the same as those of Example 1.
[0131] Examples 16 to 19
[0132] The above embodiment provides a method for manufacturing a lithium battery, and adjusts the D50 (D1) of the negative active material by adjusting the parameters of the grinding step in the manufacturing process of the negative active material (such as the current magnitude of the grinder body, etc.), and adjusts the D50 (D2) of the positive active material by adjusting the parameters of the grinding step in the manufacturing process of the positive active material (such as the current magnitude of the grinder body, etc.). The other steps and parameters are the same as those of Example 1.
[0133] Examples 20 to 23
[0134] The above embodiment provides a method for manufacturing a battery, which adjusts the powder compaction density P1 of the negative active material and the powder compaction density P2 of the positive active material by adjusting parameters such as D50, type of coke raw material, HGI, etc. The other steps and parameters are the same as those of Example 1.
[0135] Examples 24 to 28
[0136] The above examples provide the fabrication methods of the batteries, which changed the types of the positive electrode active materials, while the other steps and parameters are the same as those of Example 1.
[0137] Examples 29 to 31
[0138] The above examples provide a method for manufacturing a negative electrode sheet and a battery, which change the component content and properties of the coke raw material. The other steps and parameters are the same as those of Example 1.
[0139] The parameters and test results of each of the examples and comparative examples are shown in detail in Tables 1 to 3.
[0140] [Table 1(1)] [Table 1(2)]
[0141] [Table 2(1)] [Table 2(2)]
[0142] [Table 3(1)] [Table 3(2)]
[0143] As is clear from the test results of the above examples and comparative examples, according to the comparative examples and comparative examples, when the relationship between the non-Faraday capacity (Cdl nF) of the negative electrode sheet and the sphericity S of the negative electrode active material satisfies 0.5≦Cdl×S≦5, the battery has a relatively high energy density, better cycle performance, and relatively high magnification performance.
[0144] Comparing Examples 6 to 9 with Example 10, when 2≦r≦20 and 1.2≦0.1×r+Cdl≦10, the energy density, cycle performance, and rate performance of the battery can be improved.
[0145] Comparing Examples 11 to 13 with Examples 14 to 15, the liquid absorption time (Tmin) of the negative electrode membrane pieces and the compressed density (PDg / cm 3 When the relationship between T and PD satisfies 0.3≦T×PD≦5.8, the energy density, cycle performance and rate performance of the battery are further improved, and when 0.25≦T≦3.5, the performance of the battery is better.
[0146] Comparing Examples 16 to 18 with Example 19, when the negative electrode sheet satisfies 0.5≦Cdl×S≦5 and the relationship between the particle size D1 of the negative electrode active material and the particle size D2 of the positive electrode active material satisfies 1≦D1 / D2≦36, the positive electrode sheet and the negative electrode sheet can be endowed with better-matched electron and lithium ion transport performance, thereby further improving the performance of the lithium ion battery.
[0147] Comparing Examples 20 to 22 with Example 23, when the negative electrode sheet satisfies 0.5≦Cdl×S≦5 and the relationship between the powder compressed density P1 of the negative electrode active material at a pressure of 30 KN and the powder compressed density P2 of the positive electrode active material at a pressure of 30 KN satisfies 1.5≦P2 / P1≦2.5, it is favorable for lithium ions to diffuse inside and between the active materials, improve the solid-phase conduction ability of the lithium ions, improve the matching between the positive electrode active material and the negative electrode active material, further reduce the resistance of the lithium ion battery, and further improve the rapid charging ability and cycle life of the lithium ion battery.
[0148] The above is a detailed description of the battery and the electric device according to the embodiments of the present application, and the principles and embodiments of the present application are described using specific examples. The above description of the embodiments is for the purpose of helping the reader understand the technical solutions and their core ideas of the present application. Those skilled in the art should understand that some of the technical features described in the above embodiments may be modified or replaced with equivalents, and such modifications and replacements do not deviate from the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
Claims
1. a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode membrane piece disposed on at least one surface of the positive electrode current collector, the positive electrode membrane piece including a positive electrode active material; the negative electrode sheet includes a negative electrode current collector and a negative electrode film piece disposed on at least one surface of the negative electrode current collector, the negative electrode film piece including a negative electrode active material, the negative electrode active material including negative electrode active material granules having pores; The negative electrode sheet has a non-Faraday capacity of Cdl nF, and the negative electrode active material has a sphericity of S, where 0.5≦Cdl×S≦5 is satisfied. battery.
2. 0.5≦Cdl≦8; 10. The battery of claim 1.
3. 0.2≦S≦0.9; 10. The battery of claim 1.
4. The negative electrode active material has a pore size of r nm, and Cdl and r satisfy 1.2≦0.1×r+Cdl≦10.
10. The battery of claim 1.
5. The pore size distribution of the negative electrode active material satisfies 2≦r≦20.
5. The battery of claim 4.
6. The negative electrode active material has at least one peak in the pore size distribution in the range of 2 nm to 6 nm.
5. The battery of claim 4.
7. The liquid absorption time of the negative electrode membrane piece is Tmin, and the compressed density of the negative electrode membrane piece is PDg / cm 3 and 0.3≦T×PD≦5.8 is satisfied.
10. The battery of claim 1.
8. 0.25≦T≦3.5, and 1.1≦PD≦1.7; 8. The battery of claim 7.
9. The Dv50 of the negative electrode active material is D 1 μm, and the Dv50 of the positive electrode active material is D 2 μm, and the D 1 and the above D 2 That is, 1≦D 1 / D 2 Satisfying ≦36, 10. The battery of claim 1.
10. 6≦D 1 ≦18, 10. The battery of claim 9.
11. 0.5≦D 2 ≦8; 10. The battery of claim 9.
12. The powder compression density of the negative electrode active material at a pressure of 30 KN is P 1 g / cm 3 The powder compression density of the positive electrode active material at a pressure of 30 KN is P 2 g / cm 3 and P 1 and the above P 2 The relationship is 1.5≦P 2 / P 1 Satisfying ≦2.5, 10. The battery of claim 1.
13. 1.5≦P 1 ≦2.0, 13. The battery of claim 12.
14. 2≦P 2 ≦4; 13. The battery of claim 12.
15. The negative electrode active material includes a carbon material, and the carbon material includes graphite.
10. The battery of claim 1.
16. An electrical device comprising the battery according to any one of claims 1 to 15, the battery being used as a power supply for the electrical device. Electrical usage device.
Citation Information
Patent Citations
Secondary battery and electrochemical device
CN115528206A